(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
This study explores the professional development practices and their impact on job satisfaction among government-aided elementary school teachers in the Valsad District, Gujarat. Through a structured survey, quantitative data were collected on variables such as work hours, training participation, administrative support, and perceived value of appraisals and development programs. Findings show that while professional development is widely offered and attended, its perceived impact on teaching quality, salary, and job satisfaction remains moderate. Most teachers agree that their efforts are acknowledged, and regular appraisals are conducted, but they express skepticism regarding the tangible outcomes of those evaluations. The study highlights the need for targeted, meaningful development programs and greater alignment between appraisal systems and professional growth incentives.